2009
DOI: 10.1115/1.3147167
|View full text |Cite
|
Sign up to set email alerts
|

Mode Evolution of Cyclic Symmetric Rotors Assembled to Flexible Bearings and Housing

Abstract: This paper is to study how the vibration modes of a cyclic symmetric rotor evolve when it is assembled to a flexible housing via multiple bearing supports. Prior to assembly, the vibration modes of the rotor are classified as “balanced modes” and “unbalanced modes.” Balanced modes are those modes whose natural frequencies and mode shapes remain unchanged after the rotor is assembled to the housing via bearings. Otherwise, the vibration modes are classified as unbalanced modes. By applying fundamental theorems … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 17 publications
2
24
0
Order By: Relevance
“…Thus, the net force and moment that the absorbers exert on the rotor both vanish for the absorber modes. This agrees with the result derived by Kim et al [25] showing that a mode with phase index ka0; 1,NÀ1 is a balanced mode, i.e., a mode with no net force or moment on the rotor. The net rotor moment is not balanced (zero) for the rotational modes, and the net rotor force is not balanced for the translational modes.…”
Section: Phase Indicessupporting
confidence: 92%
See 2 more Smart Citations
“…Thus, the net force and moment that the absorbers exert on the rotor both vanish for the absorber modes. This agrees with the result derived by Kim et al [25] showing that a mode with phase index ka0; 1,NÀ1 is a balanced mode, i.e., a mode with no net force or moment on the rotor. The net rotor moment is not balanced (zero) for the rotational modes, and the net rotor force is not balanced for the translational modes.…”
Section: Phase Indicessupporting
confidence: 92%
“…The question arises whether this mode, which has the form of both Eqs. (25) and (34), should be regarded as a translational mode or an absorber mode. The answer comes from the phase index.…”
Section: Unity Tuningmentioning
confidence: 99%
See 1 more Smart Citation
“…Substitution of u kl in equation (2.5) for a chosen k into the equation that governs the motion of each substructure in equation (2.1) (that is, the L equations defined by each A The eigenvectors in equation (2.5) show that all vibration modes of a cyclically symmetric system with non-vibrating central components consist of identical motions for each substructure (i.e. the v kl ), but the substructures vibrate out of phase with the phase difference determined by the integer k, known as the phase index of the vibration mode [2,3,[23][24][25], and the spacing angles β i . (a) An example system with cyclic symmetry…”
Section: Cyclically Symmetric Systems With Non-vibrating Central Compmentioning
confidence: 99%
“…For example, Chen and Shen [15] identified that mode localization in a mistuned cyclic symmetric system will only occur when the two following conditions are met: (a) there is a group of vibration modes of the tuned cyclic symmetric rotor whose natural frequencies are nearly identical and the mode shapes have similar characteristics and (b) the vibration modes in the group contain a wide range of wave numbers. Kim et al [16] showed that the vibration modes of a rotor will evolve in a certain manner when bearings are introduced to support the rotor. Predictions of the FEA should be consistent with the conclusions drawn from these prior publications.…”
Section: Introductionmentioning
confidence: 99%